A fuzzy topsis with z-numbers and a-cut for identifying smoking factors in Jordan - Khaleel Yahia Awajan
Multi-Criteria Decision Making (MCDM) technique is considered as one of the most widely employed approaches to address and tackle the problem of decision-making. The fuzzy technique is the most known method in MCDM for Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (F-TOPSIS). Nevertheless, there are certain conditions in F - TOPSIS need to be developed and improved in the second and fifth steps. The previous F-TOPSIS still unable to define the uncertainty. Ace rdingly, this current study develops F-TOPSIS with Z-number and a-cut based On multi-criteria decision-making problem. The integration and combination of Z numbers and a-cut are considered the proper solution for the question of uncertainty as a result of the additional limitations and reliability parts. The proposed technique is applied for identifying smoking factors in Jordan. The needed data is collected from three different decision-makers: parents, students and health organizations in the form of linguistics variables. Six steps of F- TOPSIS with Z-numbers and a-cut presented in this current study to decide the ranking of the outputs. Then, a-cut ranging from (0, ... , I) is used to assess the suggested technique. The results of the study revealed that the superior alternative is A5 and the ranking order for the rest alternatives: A5 > A2 > Al > A4 > A6 > A3 where A5 is 'feel more adult', A2 is 'film star attraction', Al is 'parental influence', A4 is 'look cool/fashionable, A6 is 'parent neglect' and A3 is 'weight control', Accordingly, many of the Jordanians smoke since they feel that they are adult and mature. Moreover, the results of the correlation coefficients which are based on ten values of a-cut A I till A6 have strong positive relation since they correlate to a h other with 99%. Based on the results of the study, the F-TOPSIS with Z-numbers and a-cut presented a very fruitful strategy to handle Fuzzy Multi Criteria Decision Making (FMCDM) problems in intelligent manner since it uses Z numbers and a-cut with F-TOPSIS. Besides, it opens a rebellion in FMCDM area to supply variant strategies when dealing with decision-making problems. Thus, it provides us with different strategies and techniques in decision-making field.